An investigation into urban heat islands and their impacts on air quality in the Msunduzi municipality, KwaZulu-Natal - Maluleke, Amukelani (My University, 2019)
The active changing of the landscape through processes such as urbanisation and land use change continue to modify land and atmosphere interactions. One resulting phenomenon from these modifications is the development of urban heat islands due to increases in land surface temperature. The excessive heat retention at the surface contributes to increases in air temperatures. For polluted cities, this raises several challenges as the formation, transport and dissipation of pollutants is reliant on atmospheric thermal dynamics. The aims of this study are two-fold, firstly it aims to investigate and characterise the urban heat island effect in the Msunduzi Municipality by assessing the relationships between land surface temperature and land cover characteristics. Secondly, the study intends to provide an understanding of the contribution of the presence of the urban heat island to local air pollution in the municipality. Through the use of seasonal Landsat 8 satellite acquisitions from 2013 to 2017 and the MODIS AOD 3K product, the study applied remote sensing analysis techniques in an attempt to reach the following objectives: (i) to investigate and characterise the nature and extent of the surface urban heat island effect in the Msunduzi Municipality, (ii) to determine the relationship between land surface temperature and different land cover classes using remote sensing land cover indices and, (iii) to assess the impact on pollutant concentrations with the development of the atmospheric urban heat island whilst briefly evaluating MODIS Aerosol Optical Depth as a potential proxy for measured air pollutants in the Msunduzi Municipality. The study finds that SUHIs are clearly visible, especially during autumn and summer in concentrated patches. The generally large SUHI is predominantly located in the CBD and with isolated patches seasonally occurring over artificial surfaces and bare ground. The SUHI effect is marked during autumn (SUHI intensity = 2.65 degrees Celsius) where rural areas are notably cooler than urban areas. Built-up areas are constant sinks of heat throughout all seasons, although the SUHI is well observed during autumn. The contribution of LST to air temperature (r = 0.70; R2 = 0.49) is considerable, indicating substantial links between surface characteristics and the lower atmosphere. Assessing the seasonal NDVI, FVC and NDBI contributions to LST indicate that the presence of vegetation contributes to the cooling of the surface, with the dense location of built-up areas resulting in excessive heat retention. In some instances, especially during autumn and summer, correlations between LST and NDVI and FVC are observed at -0.839 and summer -0.735, respectively. This indicates that the presence of vegetation likely contributes to reductions in LST in contrast to built-up areas having the opposite effect. The relationships between LST, NDVI, FVC and NDBI are however moderate during other seasons and their magnitude varies between the seasons. Pollution concentrations in the municipality vary between winter and spring, with generally higher concentrations during the winter. There are marked diurnal patterns of pollutants, where high concentrations are typical during early morning periods. This is attributable to the inversion conditions dominant in the vicinity of the monitoring stations. The development of the UHI notably impacts on the cycles of pollutants, with O3 concentrations particularly sensitive to sustained increases in air temperature, especially during spring. The spatial distribution of aerosols is predominately above the Pietermaritzburg city, with fewer instances where the surrounding areas experience high AOD observations. The application of AOD as a potential proxy for air pollutants is circumstantial in this study, however it does provide better spatial assessments for aerosols and pollutants. The study concludes on the importance of understanding land and atmosphere interactions towards mitigating for climate change and creating sustainable and resilient cities.
A thesis submitted in fulfillment of the requirements for a Master of Science degree at the University of the Witwatersrand